2002
DOI: 10.1007/s11661-002-0319-7
|View full text |Cite
|
Sign up to set email alerts
|

On the constitution of the system Al-Mn-Si

Abstract: The constitution of the ternary system Al-Mn-Si over the entire composition range is investigated using metallography, X-ray diffraction (XRD), and differential thermal analysis (DTA). Ten stable ternary phase are identified and characterized. Isothermal sections for 550 ЊC and 700 ЊC, the liquidus projection, and a reaction scheme linking them are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 6 publications
7
41
0
Order By: Relevance
“…According to the study of ref. [21], it was deduced that the phases consisted of one or several metastable Al/Si/Mn compounds formed in melt spinning. The lattice parameters of α-Al in Al-Si-Mn ribbons are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study of ref. [21], it was deduced that the phases consisted of one or several metastable Al/Si/Mn compounds formed in melt spinning. The lattice parameters of α-Al in Al-Si-Mn ribbons are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Al-Si-Mn alloys have been studied because they are important mechanical engineering materials [21,22] . Fleischauer et al [23,24] prepared Al-Si-Mn crystalline and amorphous films with different compositions.…”
Section: Introductionmentioning
confidence: 99%
“…These ¢-AlFeSi particles can be ternary eutectic components which is formed by the invariant ternary eutectic reaction. 4) Figure 3 shows the typical secondary electron image of No. 1 alloy.…”
Section: Solidification Behavior Of the Low Fe Containing Alloymentioning
confidence: 99%
“…[6] However, the data reported in these studies show no general agreement. Krendelsberger et al [7] are responsible for the major contributions to the understanding of the various phase equlibria in the Al-Mn-Si system. Rand et al [8] performed a thermodynamic modeling for the Al-rich corner of the ternary system.…”
Section: Knowledge Of Phase Equilibria and Thermodynamicmentioning
confidence: 99%
“…Using differential thermal analysis (DTA) and electron probe microanalysis (EPMA) techniques, Redford et al [20] obtained the reaction temperature and phase compositions for the quasi-binary equilibrium L ϩ 8 ↔ 9 . Until the recent work by Krendelsberger et al, [7] nothing is known about the reactions that lead to the formation of the other ternary phases. Using XRD, DTA, optical microscopy, scanning electron microscopy/energy-dispersive X-ray, and EPMA methods, Krendelsberger et al [7,21] observed ten ternary compounds, measured their homogeneity ranges, characterized the crystal structures for eight ternary compounds ( 1 , 2 , 3 , 4 , 5 , 8 , 9 , and 10 ), and investigated the melting behaviors for eight ternary phases ( 1 , 2 , 3 , 4 , 6 , 8 , 9 , and 10 ).…”
Section: Evaluation Of Experimental Datamentioning
confidence: 99%